Dawud al-Fatanis thoughts on marriage in Iau l-Bab li-Muridi l-Nika bi-l-awab - Zanariah Noor (Tanjung Malim, 2021)
Dawud al-Fatanis thoughts on marriage in Iau l-Bab li-Muridi l-Nika bi-l-awab by Zanariah Noor